An overview of the lower cretaceous dinosaur tracksites from the mirambel formation in the iberian range (ne spain) - Castanera, Diego (2016)
Up to now, the ichnological vertebrate record from the Barremian Mirambel Formation (NE Spain) has remained completely unknown despite the fact that osteological findings have been reported in recent years. Here we provide an overview of 11 new dinosaur tracksites found during a fieldwork campaign in the year 2011. The majority of these tracksites (seven) preserve small- to medium-sized tridactyl tracks here assigned to indeterminate theropods. Only one footprint presents enough characters to classify it as Megalosauripus isp. Ornithopod tracks identified as Caririchnium isp. and Iguanodontipodidae indet. and sauropod tracks are recorded at two tracksites. The footprints are preserved in a variety of paleoenvironmental conditions and thus display different kinds of preservation (true tracks, shallow undertracks, natural casts and undertrack casts). The ichnological record from the Mirambel Formation seems to be theropod dominated. This is a clear discrepancy with the osteological record identified in this formation, which shows a predominance of ornithopod dinosaurs.